ChemInform Abstract: A Mild and Highly Efficient Laccase‐Mediator System for Aerobic Oxidation of Alcohols. Issue 32 (24th July 2014) - Zhu, Chenjie; Zhang, Zhi; Ding, Weiwei; Xie, Jingjing; Chen, Yong; Wu, Jinglan; Chen, Xiaochun; Ying, Hanjie
Abstract: 25 examples